Tridesetletno spremljanje bolnic s poporodnimi duševnimi motnjami - Djerzić, Amra (Medicinski razgledi, 2005)
The postpartum period is a time of rapid and fundamental biological, psychological and social changes, which can precipitate various psychiatric disorders in women. The aim of this study was to evaluate the long-term courseof postpartum psychiatric disorders that required hospitalization. Our goal was to establish the course of the illness taking into account the clinical picture of postpartum psychiatric disorders during the first hospitalization. The basic hypothesis was that women with postpartum psychiatric disorders presenting with symptoms of schizophrenia spectrum disorders during their first hospitalization would probably have had a more severe course of the disease than women presenting with symptoms of affective disorders. The sample consisted of women who were hospitalized within the first 6 months of child-birth. All these patients were hospitalized at the Ljubljana University Psychiatric Hospital during the period from 1963 to 1975.The patients were divided into two groups according to the presenting symptoms of postpartum disorders during the first hospitalization: women with schizophrenia spectrum disorders and those with affective disorders. The illness course was evaluated regarding the number and duration of hospitalizations and regularity of outpatient psychiatric treatment. The numbers of attempted suicides in both groups were also compared. The study confirmed that women with postpartum psychiatric disorders presenting with symptoms of schizophrenia spectrum disorders during their first hospitalization have a more severe course of the disease than women presentingwith symptoms of affective disorders. The final diagnosis cannot be made only on the basis of the clinical presentation of postpartum psychiatric disorders upon first hospitalization. A longer time period is necessary to be able to give a prognosis and to see whether a chronic illness will develop, aswell as to make the final diagnosis.
Keywords: Depresivna motnja; Puerperal Disorders; Depressive Disorder; Poporodno obdobje, motnje; Psihoze; Psychotic Disorders; Samomor, poskus; Schizophrenia; Shizofrenija; Suicide, Attempted; ankete; Bipolar Disorder; Hospitalizacija; Questionnaires; Hospitalization; Psihoze manično-depresivne; poporodno obdobje; depresija (medicina)